The Relationship Between The Duration of Gadget Use and Asthenopia Symptoms in Students At The X Health Vocational School, South Tangerang City - Suheti; Heni Purwanti; Royani (Jurnal Life Birth, 2026)
Background: Asthenopia or eye fatigue is a condition characterized by discomfort in the eyes, such as burning, tension, blurred vision, and difficulty maintaining visual focus. This condition often occurs due to the use of digital devices (gadgets) for a long time without sufficient rest. This study aims to: determine the relationship between the duration of gadget use and symptoms of asthenopia in students at SMK Kesehatan X, South Tangerang City. This study uses a quantitative method with a descriptive correlational design through a cross-sectional approach. The sampling technique uses stratified random sampling with a total of 74 students as respondents. The research instrument used is a questionnaire. Data analysis was carried out using the chi-square test. Research results Most respondents have a long gadget usage duration (81.1%) and 59.5% experience asthenopia. The Chi-Square test shows a p value = 0.004 (p <0.05) and OR = 7.912, so there is a significant relationship between the duration of gadget use and symptoms of asthenopia. Conclusion There is a significant relationship between the duration of gadget use and symptoms of asthenopia in students. The longer a person uses a gadget, the higher the risk of developing asthenopia.